DISSOLVED OKSYGEN LEVEL IN THE SKRIPSTI HPP DAM - Pružinska, Māra; Laizāne, Ināra (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
The aim of research was to explore the dissolved oxygen concentration on the Skripsti dam. The research was made in the vegetation period on the year of 2016. For the determination of the oxygen level in the dam was used the oximeter. Tests were made in the start of summer, in the end of summer and in the late autumn.